Jurnal Ilmiah Perlindungan dan Pemberdayaan Sosial: Kesiapsiagaan Masyarakat Dalam Menghadapi Bencana Gempa Bumi di Kecamatan Gedebage Kota Bandung - Panggita Vasthu, Rajendra; Riasih, Teta; Rosilawati, Rosilawati (Politeknik Kesejahteraan Sosial Bandung, 2024)
The 2021 Bandung City Disaster Risk Assessment (DRA) identified Gedebage Subdistrict as a high-risk area for major earthquakes. This study aimed to measure the level of community preparedness in Gedebage Subdistrict to face earthquake disasters. A quantitative method was employed to measure preparedness Data collection methods included the distribution of questionnaires, documentary analysis, and field observations. Aspects measured in preparedness include (a) knowledge of earthquake; (b) preparedness policies and guidelines; (c) emergency response plans; (d) earthquake early warning systems; and (e) resource mobilization. The population of this study was all household heads in Gedebage Subdistrict (12,217 households). A sample of 99 respondents was obtained using the Slovin formula with a 10% error rate. Sample determination was conducted using multistage sampling. In the first stage, all 43 RW in four villages in Gedebage Subdistrict were selected. In the subsequent stage, respondents were randomly selected from each RT head. The results showed that overall, the preparedness of the community in Gedebage Subdistrict was categorized as